Cannabinoid type-1 receptor signaling in dopaminergic Engrailed-1 expressing neurons modulates motivation and depressive-like behavior - Baddenhausen, Sarah; Lutz, Beat; Hofmann, Clementine (Frontiers in Molecular Neuroscience, 2024)
The endocannabinoid system comprises highly versatile signaling functions within the nervous system. It is reported to modulate the release of several neurotransmitters, consequently affecting the activity of neuronal circuits. Investigations have highlighted its roles in numerous processes, including appetite-stimulating characteristics, particularly for palatable food. Moreover, endocannabinoids are shown to fine-tune dopamine-signaled processes governing motivated behavior. Specifically, it has been demonstrated that excitatory and inhibitory inputs controlled by the cannabinoid type 1 receptor (CB1) regulate dopaminergic neurons in the mesocorticolimbic pathway. In the present study, we show that mesencephalic dopaminergic (mesDA) neurons in the ventral tegmental area (VTA) express CB1, and we investigated the consequences of specific deletion of CB1 in cells expressing the transcription factor Engrailed-1 (En1). To this end, we validated a new genetic mouse line EN1-CB1-KO, which displays a CB1 knockout in mesDA neurons beginning from their differentiation, as a tool to elucidate the functional contribution of CB1 in mesDA neurons. We revealed that EN1-CB1-KO mice display a significantly increased immobility time and shortened latency to the first immobility in the forced swim test of adult mice. Moreover, the maximal effort exerted to obtain access to chocolate-flavored pellets was significantly reduced under a progressive ratio schedule. In contrast, these mice do not differ in motor skills, anhedonia- or anxiety-like behavior compared to wild-type littermates. Taken together, these findings suggest a depressive-like or despair behavior in an inevitable situation and a lack of motivation to seek palatable food in EN1-CB1-KO mice, leading us to propose that CB1 plays an important role in the physiological functions of mesDA neurons. In particular, our data suggest that CB1 directly modifies the mesocorticolimbic pathway implicated in depressive-like/despair behavior and motivation. In contrast, the nigrostriatal pathway controlling voluntary movement seems to be unaffected.